Functionality and Comfort Design of Lower-Limb Prosthetics: A Review - Alluhydan, Khalid; Siddiqui, Md Irfanul Haque; Elkanani, Hesham (Journal of Disability Research, 2023)
This literature review on the design of amputated lower limbs has covered various aspects related to prosthetic limb design. It has highlighted the need for continuous improvement and innovation in order to enhance user satisfaction, mobility, and overall quality of life. Biomechanical factors such as gait analysis, joint range of motion, force distribution, and energy efficiency were identified as crucial considerations in amputated lower-limb design. Socket design principles, focusing on comfort and proper load distribution, were found to be essential for achieving a well-fitting and functional prosthetic limb. Emerging technologies, including advanced materials, robotics, neural interfaces, and sensor technology, were explored as potential avenues for improvement. These technologies showed promise in enhancing functionality, control, and sensory feedback in prosthetic limbs. A user-centric approach was emphasized, involving users in the design process and incorporating their feedback and preferences. Affordability and accessibility were highlighted as significant concerns, calling for the development of cost-effective solutions. Long-term performance and durability were also emphasized, stressing the need for robust materials and quality control processes. The integration of neural interfaces and sensory feedback posed opportunities and challenges for achieving more natural limb control and sensation. To sum up, this literature review has furnished valuable perspectives on amputated lower-limb design, underscoring the significance of refining design principles, accounting for biomechanical variables, embracing emerging technologies, and integrating user input. Future directions include addressing affordability, long-term performance, and neural integration while leveraging advancements in materials, technology, and user-centered design.